Efficacy of teaching physical education online: A comparative study during COVID-19 school closures - Alshammari, Salem M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of the present study was to explore the effectiveness of online teaching in Physical Education during COVID-19 school closures and to explore the thoughts and emotions evoked by COVID-19 pandemic in the physical education teachers while striving to instruct physical education virtually. This study was conducted by comparing and analyzing the variables responsible for influencing the pedagogical profession of physical education (PE) throughout Kuwait. In the present study, 60 physical education teachers of Kuwait were recruited, representing Al-Asimah school district, Hawalli school district, Al Farwaniyah school district, Al Jahra school district, Mubarak Al-Kabeer school district, and Al Ahmadi school district. Qualitative method was used for data collection in the form of specialized online surveys, as well as online focus group discussions. Statistical analysis was done using a descriptive statistical assessment and a continuous comparison approach. The findings of the present study revealed that educators comprehend that teaching PE must be done face-to-face to become meaningful, as there are multiple flaws in online instructional framework. An internet instructional approach increases the likelihood of occupational pressure and discontentment with the career path. The findings of this study may be utilized to spark a critical conversation about the challenges that PE instructors confront when teaching PE online.